Biennale di Venezia : Un secolo di storia. (Venezia : Giunti Editore, 1988)
Burri, Alberto ; Castiglioni, Davide Boriani e Livio ; De Chirico, Giorgio ; Csuri, Charles ; Ernst, Max ; Fontana, Lucio ; Giacometti, Alberto ; Kandinskij, Vasili ; Klimt, Gustav ; Matisse, Henri ; Merz, Mario ; Paolini, Giulio ; Pollock, Jackson ; Rauschenberg, Robert ; Renoir, Auguste ; Scarpa, Carlo
Italiaans
kunstcatalogus